Struktur Komunitas Ikan Ekonomis di Danau Laet Desa Subah Kecamatan Tayan Hilir Kabupaten Sanggau - Efendy, Albertina Yuniar; Adijaya, Mardan; Soetignya, Widadi Padmarsari (Jurnal Sains Mahasiswa Pertanian, 2020)
Laet Lake of ± 800 hectares totally area gives benefit to local people. The community structure of economical fish in this study tightly relative with environmental factor. The research was conducted because suitability of the approach carried out with the conditions in this Laet Lake to expect to be the relationship between local development and the economics of the people in order to management the resources in the future. The aim of this research is to determine the structure of economically valuable fish communities in Lake Laet. In this research, uses purposive sampling was used to in order to determine community structure of economical fish. There were 5 sampling side which were observed in three month; from October to December 2019. The fishing net used in the study were ¾ inch, 1 inch and 1 ½ inch size. Based on the results of study, 178 fish were caught there were 16 species and 7 families counted in number. From the research the families of Cyprinidae were the dominated fish. The gabus fish (Channa striata) and lais fish (Belodontichthys dinema) were valued as the favourite fish to local people. It was found in the study the kerandang fish (Channa pleurothalmus) and piam fish (Leptobarbus melanopterus) become frequently found as ornamental fish. The conclusion of the study were found that diversity index value is 1.93; The uniformity index value was 0.69 and the dominance index value was 0.26.